Literature Review Analisis Utilitas Biaya Terapi Adjuvan pada Pasien Kanker Payudara HER-2 Positif - Udin, Baha; Yusransyah, Yusransyah; Anita Nugraheni, Diesty (JURNAL FARMASI GALENIKA, 2024)
Breast cancer is one of the diseases that causes death in women in the world. The high costs incurred to control cancer can affect the control of other diseases. One of the therapies given to breast cancer patients is adjuvant therapy. This review article aims to determine the cost utility of adjuvant therapy in Human Epidermal Growth Factor Receptor-2 (HER-2) Positive breast cancer patients in various countries. The article review method used is a literature review by conducting a literature study using the Pubmed and Google Scholar data bases. After conducting a literature study, 37 articles were obtained but only 4 articles met the inclusion and exclusion criteria. The articles used are articles that discuss the comparison of cost-effectiveness with quality of life as a clinical outcome of adjuvant therapy used by HER-2 Positive breast cancer patients. The articles used were conducted in 4 countries, namely the United States, Japan, the Philippines and Brazil. The results of the review of each article used show that each country has different strategies regarding costs for providing adjuvant therapy to HER-2 Positive breast cancer patients. The use of adjuvant therapy with the highest total costs, namely trastuzumab emtansine (T-DM1) in the United States (USD 218,179.98). The highest ICER value in this review article is a comparison of trastuzumab alone with the combination trastuzumab-neratinib (USD 416,106) in the United States. The therapy that produced the highest clinical outcome value of quality of life was T-DM1 (17,310) in Brazil and the United States. There is a comparison of the total cost and effectiveness of adjuvant therapy for HER-2 positive breast cancer. Differences in total costs and cost-effectiveness are influenced by research time, population, policies related to determining minimum treatment costs, currency, and research methods.